Discrete Wavelet Transformation Approach for Surface Defects Detection in Friction Stir Welded Joints - Mishra, Akshansh (Fatigue of aircraft structures, 2020)
Friction Stir Welding joint quality depends on input parameters such as tool rotational speed, tool traverse speed, tool tilt angle and an axial force. Surface defects formation occurs when these input parameters are not selected properly. The main objective of the recent paper is to develop Discrete Wavelet Transform algorithm by using Python programming and further subject it to the Friction Stir Welded samples for the identification of various external surface defects present.